A CROSS SECTIONAL STUDY OF ADVERSE DRUG REACTIONS IN A TERTIARY CARE TEACHING HOSPITAL - KALA.P; JAMUNA RANI.R; SANGEETHA RAJA (International Journal of Pharma and Bio Sciences, 2015)
The aim of this study was to carry out Adverse Drug Reactions (ADRs) monitoring in various departments of a tertiary care teaching hospital. Methods: A cross sectional study was carried out on ADRs in a tertiary care teaching hospital in Potheri from June to December 2013 after Institutional Ethics Committee approval. Result: Total 32 ADRs were reported. Among them, 46.87% were in males and 53.12% were in females. The majority of ADRs were due to antimicrobial agents (71.78%) followed by antiepileptics (18.75%). Maximum number of patients (81.25%) was reported with dermatological manifestations. Highest number of ADRs was reported from the department of medicine (37.5%). As per Naranjo’s probability scale, 50% reports were assessed as possible and 46% as probable. 75% reports were documented as moderate according to Modified Hartwig’s criteria for severity assessment. The present study was done to emphasize the importance of pharmacovigilance among practicing physicians.